Periodic patterning of the Drosophila eye is stabilized by the diffusible activator Scabrous - Avishai Gavish (Nature Portfolio, 2016)
Patterning in the Drosophila eye is achieved by a series of signalling cascades over several cell distances. Here Gavish et al.model lateral inhibition in the developing eye to understand how developmental noise refines such patterning, identifying a novel activator required for buffering spatial variability.